2004
DOI: 10.1111/j.1520-037x.2004.3117.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nonsteroidal Anti‐Inflammatory Medications for Prevention of Atrial Fibrillation Following Coronary Artery Bypass Graft Surgery

Abstract: This study was designed to test whether nonsteroidal anti-inflammatory medications could reduce the frequency of atrial fibrillation after coronary artery bypass graft surgery. The study was designed as an open-label, randomized trial. Patients undergoing first-time coronary artery bypass graft surgery were considered eligible. Patients with a history of atrial fibrillation, serum creatinine >2.0 mg/dL, on antiarrhythmic treatment, and those undergoing concomitant valvular surgery were excluded. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 31 publications
0
28
0
3
Order By: Relevance
“…Other factors associated to POAF in the literature include history of chronic obstructive pulmonary disease, heart failure, diabetes mellitus, valvulopathy, withdrawal of ACE inhibitors or beta-blockers [2,47] and obesity [48]. In contrast, preoperative use of statins [49,50], beta-blockers [51], amiodarone [52] and anti-inflammatory agents [53,54] has been associated with a reduced incidence of POAF. However, it is still controversial whether these interventions impact significantly on the perioperative complications derived from atrial fibrillation and whether these benefits outweigh the potential risk associated to its use [7].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors associated to POAF in the literature include history of chronic obstructive pulmonary disease, heart failure, diabetes mellitus, valvulopathy, withdrawal of ACE inhibitors or beta-blockers [2,47] and obesity [48]. In contrast, preoperative use of statins [49,50], beta-blockers [51], amiodarone [52] and anti-inflammatory agents [53,54] has been associated with a reduced incidence of POAF. However, it is still controversial whether these interventions impact significantly on the perioperative complications derived from atrial fibrillation and whether these benefits outweigh the potential risk associated to its use [7].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, some reports indicate that NSAIDs, such as salicylic acid (SA), can reduce ventricular dysfunction and arrhythmias [16][17][18] . The investigators proposed that ibuprofen could prevent the atrial fibrillation mediated by inflammation, and SA could trap the hydroxyl radicals to reduce postischemic ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Data from retrospective studies as well as RCTs indicate that NSAIDs are effective at reducing the risk of POAF by as much as 65%, although adequate numbers of patients have not been studied to determine their impact on LOS and stroke, nor to fully evaluate the safety of these agents following cardiothoracic surgery. 54,55 A prospective, nested cohort study of 555 patients from the Atrial Fibrillation Suppression Trials (AFIST) I, II, and III demonstrated that the incidence of POAF was significantly reduced in patients who receive NSAIDs postoperatively (adjusted odds ratio [AOR] 0.54, 95% CI 0.32-0.90; P ¼ .02) in a multivariate analysis. No significant effects on stroke (AOR 1.10, 95% CI 0.21-5.66) or myocardial infarctions (AOR 1.70, 95% CI 0.40-7.10) were seen, although few events occurred.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%